Communication networks and protests: investigating the “Occupy Movement” in the United States - AMORIM, Guilherme Marques de (2016)
This article investigates the influence of broadband Internet availability in the occurrence of events of civil unrest, both with theory and empirical evidence. We first expand a recent model of protests considering the hypothesis that the Internet sets an environment for communication and information exchange that boosts collective dissatisfaction towards unfair policies. We then use collected data on the locations of 2011’s Occupy Movement in the United States to estimate the impact of one extra Internet Service Provider on the probability of evidencing protests in a given location. To identify the effect of broadband provision, we use an instrumental variable approach based on topographic elevation as a source of exogenous variations in the cost of building and maintaining cable infrastructure. As an alternative approach, we also use identification through heteroskedasticity, which does not rely on exclusion restrictions. In accordance with our theoretical predictions, our results show that the availability of broadband services during the time of the Occupy protests was greatly associated with the occurrence of such events.